The Wiley-Blackwell handbook of childhood social development - Smith, Peter K.; Hart, Craig H., 1957-; Wiley InterScience (Online service) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
'Building on the success of the highly acclaimed first edition, The Wiley-Blackwell Handbook of Childhood Social Development, Second Edition continues with its presentation of the most thorough, authoritative, and up-to-date overview of research and theory concerning children's social development from pre-school age to the onset of adolescence. Contributions from an international cast of leading experts in their respective fields incorporate the latest findings and developments in each of the topics covered in the first edition - ranging from the family context, the peer group, social skills and social cognition, play, helping and moral reasoning to cooperation, competition, aggression and bullying, as well as children with special needs. This new edition is revised and updated throughout; it includes new chapters on issues such as children and the environment, cultural influences, the history of childhood, interventions, and neuro-psychological perspectives. Each chapter summarizes existing knowledge in the field, synthesizing the latest research in an accessible manner, while at the same time highlighting areas of emerging interest and growing debate. Editorial commentaries prefacing each section provide further synthesis and clarity for the topics covered. The Wiley-Blackwell Handbook of Childhood Social Development, Second Edition presents students, practitioners, and researchers alike with an invaluable resource for accessing the latest research and theories that shape our understanding of the social development of children'--Provided by publisher.
Historical Overview. Part Introduction -- Historical Perspectives on Contemporary Research in Social Development / W Andrew Collins -- Disciplinary Perspectives on Social Development. Part Introduction -- Behavioral Genetics / Alice M Gregory, Harriet A Ball, Tanya M M Button -- Conceptual Development and Emotion: A Neuropsychological Perspective / Steven Woltering, Marc D Lewis -- Evolutionary Perspectives on Social Development / David F Bjorklund, Anthony D Pellegrini -- Historical Reframing of Childhood / Willem Koops -- Cultural Psychological Perspectives on Social Development in Childhood / Heidi Fung -- Sociological Perspectives on Social Development / Gerald Handel -- Ecological Contexts for Social Development. Part Introduction -- Culture and Social Development / Xinyin Chen, Janet Chung, Rachel Lechcier-Kimel, Doran French -- The Social Development of Immigrant Children: A Focus on Asian and Hispanic Children in the United States / Charissa S L Cheah, Christy Y Y Leung -- Children's Interpersonal Skills and School-Based Relationships / Gary W Ladd, Becky Kochenderfer-Ladd, Ann-Margret Rydell -- Environmental Psychology / Christopher Spencer, Kate Gee -- Child and Contextual Factors in Social Development. Part Introduction -- Temperament and Social Development / Ann Sanson, Sheryl A Hemphill, Bilge Yagmurlu, Sandee McClowry -- Children's Social Development within the Socialization Context of Child Care and Early Childhood Education / Carollee Howes -- The Interplay Between Parents and Peers as Socializing Influences in Children's Development / Stephanie M Reich, Deborah Lowe Vandell -- Sex Differences in Social Behavior / Vickie Pasterski, Susan Golombok, Melissa Hines -- Ethnicity, Race, and Children's Social Development / Stephen M Quintana -- Family Context. Part Introduction -- Parent-Child Attachment in Early and Middle Childhood / Laura E Brumariu, Kathryn A Kerns -- Parent-Child Relationships and Influences / Alan Russell -- Sibling Relations in Early and Middle Childhood / Nina Howe, Hildy S Ross, Holly Recchia -- Peer Group. Part Introduction -- Social Status Among Peers: From Sociometric Attraction to Peer Acceptance to Perceived Popularity / Shelley Hymel, Leanna M Closson, Simona C S Caravita, Tracy Vaillancourt -- Social Skills and Social Competence in Interactions with Peers / Antonius H N Cillessen, Amy D Bellmore -- Emotions and Social Development in Childhood / Susanne Denham, Heather Warren, Maria von Salisch, Oana Benga, Jui-Chih Chin, Elena Geangu -- Social Withdrawal and Shyness / Kenneth H Rubin, Robert J Coplan, Julie C Bowker, Melissa Menzer -- Play, Cooperation, Competition, Aggression, and Bullying. Part Introduction -- Social Play / Thomas G Power -- Cooperation and Competition / Barry H Schneider, Joyce Benenson, Marta Filip, Mihaly Berkics, Monika S̀ndor -- Aggression in Children / Sarah M Coyne, David A Nelson, Marion Underwood -- Bullying / Christina Salmivalli, Katlin Peets, Ernest V E Hodges -- Cognition, Helping, and Moral Reasoning. Part Introduction -- Social Cognition / Charlie Lewis, Jeremy Carpendale -- Prosocial Behavior / Joan E Grusec, Paul Hastings, Alisa Almas -- Children's Social and Moral Reasoning / Charles C Helwig, Elliot Turiel -- Children's Understanding of Society / Martyn Barrett, Eithne Buchanan-Barrow -- Intervening in Social Development. Part Introduction -- Intervening in Childhood Social Development / Mary Ellen Voegler-Lee, Janis B Kupersmidt -- The Development of Social Competence in Children With Disabilities / Karen E Diamond, Hsin-Hui Huang, Elizabeth A Steed -- Interventions for Development of Social Skills among Children in Developing Countries / Suman Verma, Rajani Konantambigi.
Includes bibliographical references and indexes.
Print version record.
Keywords: Developmental psychology -- Social aspects; Child psychology -- Social aspects; Child psychology -- Social aspects; Developmental psychology -- Social aspects; Electronic books